Hammers, Axes, Bulls, and Blood: Some Practical Aspects of Roman Animal Sacrifice*. (21st May 2014) - Aldrete, Gregory S.
Abstract: Animal sacrifice was a central component of ancient Roman religion, but scholars have tended to focus on the symbolic aspects of these rituals, while glossing over the practical challenges involved in killing large, potentially unruly creatures, such as bulls. The traditional explanation is that the animal was struck on the head with a hammer or an axe to stun it, then had its throat cut. Precisely how axes, hammers, and knives were employed remains unexplained. This article draws upon ancient sculpture, comparative historical sources, and animal physiology to argue that the standard interpretation is incomplete, and, in its place, offers a detailed analysis of exactly how the killing and bleeding of bovines was accomplished and the distinct purposes of hammers and axes within these rituals.